Exposure hazards of As in semi-urban rivers of Anambra, South-East Nigeria: Concentrations, source apportionments, health risks, and irrigation quality assessments - Christian Chukwuemeka Oli; Chideraa Courage Offor; Emeka Christian Ezeudu; Chinecherem Lilian Muotanya (HydroResearch)
The assessment of As and other water quality parameters (Fe, Mn, K+, Na+, Mg2+, Ca2+, Cl−, SO42−, PO43−, NO3−, BOD, EC, TSS, TDS, and turbidity) in the four rivers of Anambra State, Nigeria, was carried out in order to ascertain their human health risks. The results showed that As and Fe (mg/L) ranged from 0.00 to 1.39 and 0.10 to 0.26 respectively (September) and from 0.06 to 0.98 and 0.07 to 0.29 in October. As concentrations in the rivers followed the order: Obibia > Mmiri-Ukwaka > Ovia > Mmiri-Eze, and were all above the WHO permissible limit (0.01 mg/L). Ovia, Obibia, and Mmiri-Ukwaka Rivers had WAWQI >100, indicating unsafe water. As had HQing > 1 in all the rivers except in Mmiri-Eze. The strong positive correlation between As and Fe suggest their geogenic origin; hence these rivers should be treated with activated carbon before consumption.